An analytical translation study of social linguistic aspects in Dominiga's Arabic version - Alwan, Haifa Hussein; Muhassin, Mohamed Hashem (Al-Adab Journal, 2021)
The aim of our current research is to analyze the socio – linguistic aspects such as (age, gender, place, time, race, proper names, food names, moral and educational values) in the translation of Dominiga's novel by the Spanish writer Gonthaloa Torrenta Payster (1999). The translator's way of conveying those values to readers of young ages and youth. In this analysis, we have relied on the classification of the humanities and English translation, Andrew Chesterman. This classification includes sixteen variables, and each of these variables has a default value that has been classified into 4 groups which are (balance variables, language variables, translator variables and finally structural frame variables for the translated text). We raise several questions, including:- What are the considerations that the translator should take into account when translating for children and youth?- What knowledge and sciences must a translator possess in order to convey the main idea of the original text to readers of young ages and youth?- Is it possible for anyone with sufficient linguistic knowledge to translate a work directed at children and youth, or does he need to be familiar with the psychological, mental and social aspects of this category of readers? Each society has its own customs, traditions, ideas and beliefs that distinguish it from other societies. Here , the translating must take into account these aspects when translating any literary work from one language to another , especially if this work is intended for children , adolescents and youth , due to the importance and danger of these age stages and their impact on the formation of the personality of the child and young person , and directing it towards the right direction and avoiding all stories and novels that carry ideas that contradict the concepts and beliefs of the society in which the young reader lives . Therefore, the researcher wants to present through this research information, observations, analysis and strategies that the translator used when translating these aspects, and whether he used the correct method in translation or not.